Male duct ectasia associated with HIV infection. Issue 1 (February 1996) - Downs, A M; Fisher, M; Tomlinson, D; Tanner, A
Abstract : The incidence of male duct ectasia (periductal mastitis) is extremely rare, only eight cases having been reported. The underlying cause (as in females) is uncertain. Two cases in HIV positive males of recurrent unilateral nipple lesions are reported with histology consistent with duct ectasia. At presentation neither patient had an AIDS defining illness. An impaired immunity secondary to HIV infection may result in an increased susceptibility to repeated nipple infections, and the clinical as well as histological features of duct ectasia. The consideration of HIV infection in future cases of male duct ectasia may be warranted.